The tripartite Ramsey numbers rt(C4;2) and rt(C4;3) - S. Buada (2018)
© 2015, Forum-Editrice Universitaria Udinese SRL. All rigths reserved. The k-colored tripartite Ramsey numbers r t (G; k) is the smallest positive integer n such that any k-coloring of lines of a complete tripartite graph K n,n,n there always exists a monochromatic subgraph isomorphic to G. When G is C 4 it is known, but unpublished in a journal, that r t (C 4 ; 2) = 3. In this paper we simplify the proof of r t (C 4 ; 2) = 3 and show the new result that r t (C 4 ; 3) = 7.